2008
DOI: 10.1038/ncpcardio1054
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma: cyclic attacks of hypertension alternating with hypotension

Abstract: Intravenous phentolamine and fluids, oral doxazosin and surgical removal of the tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…There are case reports describing alternating cycles of hypertension and hypotension as a manifestation of pheochromocytoma. 3,4 To our knowledge, the short cyclic intervals seen in our case have not been reported before. A similar case reported by Otsuka et al 5 showed a periodic fluctuation of blood pressure with cyclic changes at 20 min intervals and transient LV apical ballooning in pheochromocytoma.…”
supporting
confidence: 43%
“…There are case reports describing alternating cycles of hypertension and hypotension as a manifestation of pheochromocytoma. 3,4 To our knowledge, the short cyclic intervals seen in our case have not been reported before. A similar case reported by Otsuka et al 5 showed a periodic fluctuation of blood pressure with cyclic changes at 20 min intervals and transient LV apical ballooning in pheochromocytoma.…”
supporting
confidence: 43%
“…[45] As with paroxysmal hypertension, these patients had tumors which secreted primarily epinephrine. [46] While the pathophysiology for this event is unclear, it is suggested that baroreceptors respond to a rapid rise in BP during acute paroxysm with activation of the negative feedback loop via both the sympathetic and parasympathetic systems, causing a rapid decrease in BP. [45-46]…”
Section: Clinical Pattern Of Pheochromocytoma-related Hypertensionmentioning
confidence: 99%
“…Oishi et al have reported treating a similar case successfully with a selective α-blocker ( 7 ). Kobal et al , in a study of nine cases, have reported the use of α-blockers in all cases and their effectiveness in controlling BP fluctuation in five of the nine cases ( 8 ). Recently, Ionescu et al have reported the successful treatment of pheochromocytoma with rapid alternating cycles of hypertension and hypotension using metirosine administration that inhibited catecholamine synthesis ( 9 ).…”
Section: Discussionmentioning
confidence: 99%